Establishment and spread of Gyranusoidea tebygi Noyes and Anagyrus mangicola Noyes (Hymenoptera: Encyrtidae), two biologigal control agents released against the mango mealybug Rastrococcus invadens Williams (Homoptera: Pseudococcidae) in Africa - Neuenschwander, Peter; Boavida, C.; Bokonon-Ganta, A.H.; Gado, A.; Herren, H.R. (Informa UK Limited, 1994)
Two specific endophagous parasitoids Gyranusoidea tebygi and Anagyrus mangicola, of Indian origin, were mass‐reared at the International Institute of Tropical Agriculture in Cotonou and released against the mango mealybug Rastrococcus invadens, in collaboration with national biological control programmes. G. tebygi was released in the following countries: Benin, Gabon, Ghana, Nigeria, Sierra Leone and Zaire. In Togo, it had been released earlier and studied during another project. This parasitoid is now established in all areas infested by the mango mealybug. In addition, it established itself without previous release in Congo and Côte d'Ivoire. A. mangicola has been released in Benin, Gabon and Sierra Leone since 1991, and by mid‐1993 was recovered from a few sites. It seems locally established in southern Benin.